Male earnings inequality, women’s employment and family income inequality in Australia, 1982 – 2007 - Austen, Siobhan; Redmond, G. (Centre for Research in Applied Economics, 2012)
This paper uses cross-sectional data to examine the relationship between the growth in earnings inequality among men, changes in women’s earnings and changes in family income inequality in Australia between 1982 and 2007-08. Male earnings inequality increased substantially across this period, as did women’s participation in paid work. Our analysis shows that both impacted on family income inequality, which rose by a relatively small amount. We also show that the impact of changes in women’s employment and earnings on family income inequality changed over the study period. During the years associated with the Hawke-Keating Labor government (1982 to 1995-96), growth in women’s earnings pushed family income inequality higher. However, during the tenure of the Howard government (1995-96 to 2007-08) the pattern reversed, with continued growth in women’s earnings contributing a moderating influence on family income inequality. These findings deliver new evidence on the importance of trends in family formation and the correlation of husbands’ and wives’ earnings to the evolution of family income inequality. They also show the potential effects of a range of policy initiatives on this evolution.